O silêncio retórico das personagens de Vidas Secas - Duarte, Maria Júlia Santos (2018)
The study of Rhetoric refers to Antiquity with Aristotle, who considers the faculty to generate persuasion through discourse. However, Le Breton (1997) advocates that silence is a form of communication in which a minimum of words is required to ensure the connection between individuals. In this sense, silence has nuances that are in between the lines of saying to cause senses. This research analyzes, from a rhetorical perspective, the silence of the characters in the work Vidas Secas by Graciliano Ramos. The methodology used is the literature review based on Aristotle (s.d.), Perelman and Olbrechts- Tyteca (1996), Le Breton (1997), Orlandi (1997), Ferreira (2010), among other researchers in the field of Rhetoric and silence. The study is based on the analysis of fragments of this work, through the identification of figures, rhetorical places, ethos of the characters of Vidas Secas, among other categories of analysis that evidence rhetorical silence as an argumentative discourse. The results obtained identify the importance of silence in rhetorical argumentation, as well as the fact that silence provides interaction between the speaker and the audience